2002
DOI: 10.1128/jvi.76.15.7365-7373.2002
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus-Specific CD8+T Cells in Human Breast Milk

Abstract: Breast-feeding infants of human immunodeficiency virus (HIV)-؉ T cells mediated these responses, and a chromium-release assay showed that these BMC were capable of lysing target cells in an HIV-specific manner. These data demonstrate the presence of HIV-specific major histocompatibility complex class I-restricted CD8 ؉ CTLs in breast milk. Their presence suggests a role in limiting transmission and provides a rationale for vaccine strategies to enhance these responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 56 publications
7
46
1
Order By: Relevance
“…All displayed increased frequency of tetramer binding T cells in breast milk when compared with PBMC (Table I). This is consistent with our prior studies wherein we found that the tetramer frequency in blood was only 0.22% compared with 0.65% in breast milk (12).…”
Section: Ag-specific Ifn-␥-secreting Cd8supporting
confidence: 82%
See 3 more Smart Citations
“…All displayed increased frequency of tetramer binding T cells in breast milk when compared with PBMC (Table I). This is consistent with our prior studies wherein we found that the tetramer frequency in blood was only 0.22% compared with 0.65% in breast milk (12).…”
Section: Ag-specific Ifn-␥-secreting Cd8supporting
confidence: 82%
“…Milk samples were kept at 4°C for no Ͼ5 h and then milk was centrifuged at 400 ϫ g for 15 min. Cream that formed at the top was scooped out with a sterile spatula, milk supernatant was saved for viral load determinations, and the cell pellet was washed two times with HBSS (12). Cells were resuspended in complete RPMI 1640 with 10% AB sera and viable BMC were counted using a hemocytometer by trypan blue exclusion.…”
Section: Isolation Of Breast Milk Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…[40][41][42] A specific oligosaccharide epitope in breast milk, Lewis X component, was recently discovered to be able to bind to dendritic cell-specific ICAM3-grabbing nonintegrin (DC-SIGN), thereby inhibiting HIV transfer to CD4 cells. 43 Further study of other breast milk parameters, including of HIV-specific cellular immune responses 44,45 and innate immune factors, remains important to further understanding of how to make breast-feeding safer. …”
Section: Discussionmentioning
confidence: 99%